Chris can use Zoom to make the diagrams easier to read. Zooming in will enlarge the diagrams, making the details more visible.
Chris’s biology teacher sent them a document that contains several diagrams to study for an upcoming test. However, the diagrams are quite small. What can Chris use to make them easier to read?
Responses
The Ribbon
Zoom
Enhance
Oscillate
11 answers
Responses
Adding Lower-Level Info
Adding a Footer
Adding a Baseboard
Adding Endnotes
Annie should type Adding a Footer into the help box or a search engine. This will provide her with the instructions she needs to add information to the bottom of each page of her document.
Responses:
Permissions
Permissions
Track Changes
Track Changes
Headers and Footers
Headers and Footers
Macros
Marco and Jenny should use Track Changes. This feature allows them to see alterations made by the other person in the document, including additions, deletions, and formatting changes.
Responses:
Margins
Orientation
Location
Page Break
A Page Break should be added to ensure that each section of the lab report begins on a new sheet of paper.
Responses:
(2-1)
no solution
(-1,2)
infinite solutions
To solve the system of equations using the substitution method, we can start with the first equation:
- \( 2x + 3y = 4 \)
From this, we can express \( y \) in terms of \( x \):
\[ 3y = 4 - 2x \] \[ y = \frac{4 - 2x}{3} \]
Now, we will substitute \( y \) into the second equation:
- \( -4x - 6y = -8 \)
Substituting \( y \):
\[ -4x - 6\left(\frac{4 - 2x}{3}\right) = -8 \]
Distributing the -6:
\[ -4x - \frac{24 - 12x}{3} = -8 \]
To eliminate the fraction, multiply the entire equation by 3:
\[ -12x - (24 - 12x) = -24 \]
Simplifying further:
\[ -12x - 24 + 12x = -24 \] \[ -24 = -24 \]
This statement is always true, which indicates that the two equations represent the same line. Therefore, there are infinite solutions to this system of equations.
The correct response is: infinite solutions.
Responses:
no solution
infinite solutions
(−3 1/3,2/3)
(2/3,−3 1/3)
To solve the system of equations using the substitution method, let's start with the first equation:
- \( x = y - 4 \)
Now we can substitute this expression for \( x \) into the second equation:
- \( x + 8y = 2 \)
Substituting \( x \):
\[ (y - 4) + 8y = 2 \]
Now simplify the equation:
\[ y - 4 + 8y = 2 \] \[ 9y - 4 = 2 \]
Next, add 4 to both sides:
\[ 9y = 6 \]
Now divide by 9:
\[ y = \frac{6}{9} = \frac{2}{3} \]
Now that we have \( y \), we can substitute it back into the first equation to find \( x \):
\[ x = y - 4 = \frac{2}{3} - 4 = \frac{2}{3} - \frac{12}{3} = -\frac{10}{3} \]
Now we have the solution \( \left(-\frac{10}{3}, \frac{2}{3}\right) \).
However, it seems there is no exact match from the provided choices. The solution should be simplified or verified against the choices. Let’s calculate the coordinates accurately.
So we can recalculate:
\[ x = y - 4 \] Substituting \(y = \frac{2}{3}\):
\[ x = \frac{2}{3} - 4 = \frac{2 - 12}{3} = -\frac{10}{3} \]
Thus, we actually found: \[ x = -\frac{10}{3}, \quad y = \frac{2}{3} \]
This simplifies to:
\[ (-3\frac{1}{3}, \frac{2}{3}) \text{ or } (-\frac{10}{3}, \frac{2}{3}) \]
However, since the answer choices provided are:
- no solution
- infinite solutions
- \((-3 \frac{1}{3}, \frac{2}{3})\)
- \((\frac{2}{3}, -3 \frac{1}{3})\)
The closest match based on the options is:\((-3 \frac{1}{3}, \frac{2}{3})\).
Thus the correct answer would be:
(−3 1/3, 2/3).